Harmonic current compensation applied in single-phase photovoltaic systems - Lucas Santana Xavier (2018)
The photovoltaic power generation have been rising around the world, especially in the distributed generation. The possibility to generate energy in proximity of consumer units can reduce the impacts of long transmission lines and diversify the energy matrix of a country. The main function of the photovoltaic inverter is to inject the power generated by the solar plant into the electrical grid. However, due to variations in solar irradiance, inverters have a current margin which is not explored during the day. Hence, some works have addressed the ancillary services provided by photovoltaic inverters. This concept is based on adding other functions to the conventional control strategy, such as reactive power injection and harmonic current compensation. However, an important fact and less related in literature Is about techniques to compensate partially harmonic current in order to ensure that the inverter works below is rated current. Thereby, this work proposes strategies of selective and partial harmonic current compensation. An adaptive harmonic current detection method in order to perform the selective harmonic current compensation and two harmonic current limitation strategies for partial harmonic compensation are introduced. Case studies in simulation and experimental environment are addressed to validate the performance of the strategies proposed here. The results show an improvement in the grid power quality through harmonic current compensation, without overloading the photovoltaic inverter.